Pharmacovigilance of quality deviations in the public healthcare system - Carolina Resende Bitencourt; Cristiane Aparecida Menezes De Pádua; Paula Lana De Miranda Drummond; Edson Perini (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2018)
Drug quality deviation (DQD) is the disagreement with the parameters at the registration with after commercialization step. Pharmacovigilance programs should be notified of DQD to ensure drug efficacy and support patient safety. Objective: To describe DQD from public healthcare system and its impact on the pharmaceutical service. Methods: Descriptive analysis of DQD recorded at Belo Horizonte primary and secondary care facilities, from April to September 2016. Variables: Type of DQD, pharmaceutical product, therapeutic class, notifying health unit, risk classification, and reply of DQD notification. This analysis was described by measures of central tendency and dispersion. Results: 329 DQD in 271 notifications were recorded leading to a loss of 9,311 preparations, representing on average 0.2% of the purchased lot. Most DQD were recorded at the primary health care level in solid preparations. Drug-related problems included deviations in package content (47%), package integrity (26%), label (5%), and pharmaceutical product itself (22%). Anti-infectives for systemic use (21%) and nervous system drugs (20,3%) were the main therapeutical classes. Approximately 70% of the DQD were classified as of intermediate risk. Drug suppliers replied 83.6% of notifications. No notification has been completely analyzed by the sanitary surveillance. Conclusions: Pharmacovigilance is an important tool to minimize potential harm to the patient, since it prevents inappropriate medications from being made available for dispensing. DQD management also helps to minimize financial losses. The strengthening of this activity in all healthcare services also contributes to regulatory actions at the national level.